1978
DOI: 10.1007/bf02533593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol ingestion and dietary fat levels on mitochondrial lipids in male and female rats

Abstract: The effects of sex, dietary fat levels, and ethanol ingestion on rat liver mitochondrial lipids have been studied. Two groups of male animals were fed either a low‐fat diet for about 76 days or a high‐fat diet for about 52 days, and two groups of female animals were fed the same low‐fat diet for about 50 days or the high‐fat diet for about 37 days. Ethanol was substituted isocalorically for carbohydrate and amounted to 36% of total calories. The total as well as individual concentrations of fatty acids, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…This decrease in the ratio of 20:4w6 to linoleic acid (1 8:2w6) with ethanol was also observed in other studies with rats (3,4) and humans (5,6), although the effect of ethanol on fatty acid profile was variable among tissues and lipid fractions.…”
Section: Introductionsupporting
confidence: 84%
“…This decrease in the ratio of 20:4w6 to linoleic acid (1 8:2w6) with ethanol was also observed in other studies with rats (3,4) and humans (5,6), although the effect of ethanol on fatty acid profile was variable among tissues and lipid fractions.…”
Section: Introductionsupporting
confidence: 84%
“…The diet consisted of corn oil (37% of calories), protein (23%), carbohydrate, minerals, vitamins, and ethanol (ethanol diet) or isocaloric dextrin-maltose (control diet) supplemented with lipotropes. 12,13 OTC (a kind gift from Cynthia Leaf, Transcend Therapeutics) was added to the diet at a dose of 500 mg/kg/d. 10 The ethanol concentration ranged between 7% and 9% vol/vol depending on the demonstrated degree of intoxication and the urine alcohol concentration.…”
Section: Methodsmentioning
confidence: 99%
“…approximately 50/50 mixture of α-hydroxyethyl and lipid-derived free radical adducts (4,26). ESR studies of such systems using 13 C-ethanol have demonstrated the similarity of the hyperfine coupling constants and the presence of both radical adducts following chronic ethanol administration using Tsukamoto-French protocol (4). Spectrum II, with its unique β hydrogen hyperfine coupling of 3.2 G, is most likely the POBN/CO 2 • -free radical adduct formed by the abstraction of a hydrogen atom from endogenous formate to give CO 2 • -, which then reacts with POBN (27).…”
Section: Figurementioning
confidence: 99%